Accessory Cr-Spinels in the Section of the Nude-Poaz Massif in the Monchegorsk (2.5 Ga) Mafic-Ultramafic Layered Complex (Kola Peninsula, Russia): Comparison with Ore-Forming Chromites - Tatiana Rundkvist; Pavel Pripachkin (Minerals, 2021)
The paper studies accessory Cr-spinels from deep drill holes crossing the Nude-Poaz massif, which is a part of the Monchegorsk mafic-ultramafic layered complex (2.5 Ga, Kola Peninsula, Russia). Cr-spinels occur as two morphological types that differ in their chemical composition, i.e., Cr-spinels of the first type are more aluminous, while Cr-spinels of the second type are more ferruginous and titaniferous. Cr-spinels of the Nude-Poaz massif are characterized by a Fe-Ti trend known for layered intrusions in the world. Cr-spinels of the Nude-Poaz massif quite clearly differ in composition from chromites of the Sopcheozero deposit: they are more ferruginous and less chromous. The specific composition of Cr-spinels in rocks of the Nude-Poaz massif can be correlated with the sequence of the magmatic phases intrusion.